2020
DOI: 10.3390/cancers12020438
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Melanoma Hypoxia with the Food-Grade Lactic Acid Bacterium Lactococcus Lactis

Abstract: Melanoma is the most aggressive form of skin cancer. Hypoxia is a feature of the tumor microenvironment that reduces efficacy of immuno- and chemotherapies, resulting in poor clinical outcomes. Lactococcus lactis is a facultative anaerobic gram-positive lactic acid bacterium (LAB) that is Generally Recognized as Safe (GRAS). Recently, the use of LAB as a delivery vehicle has emerged as an alternative strategy to deliver therapeutic molecules; therefore, we investigated whether L. lactis can target and localize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 61 publications
0
4
0
Order By: Relevance
“…Therefore, optoacoustic imaging allows to differentiate between single skin layers (SC, viable epidermis and dermis) and enables visualization of the blood capillary loops and the vascular plexus (impact of the vascular barrier on drug delivery). Addressing cancer-induced morphologic (e.g., angiogenesis) or metabolic changes (e.g., tissue glycation) within the skin, several studies already document the applicability of optoacoustic imaging for diagnostic purposes [ 190 , 191 , 192 ] or potentially cancer-related changes of tissue glycation [ 193 ].…”
Section: And How Can We Measure Them?mentioning
confidence: 99%
“…Therefore, optoacoustic imaging allows to differentiate between single skin layers (SC, viable epidermis and dermis) and enables visualization of the blood capillary loops and the vascular plexus (impact of the vascular barrier on drug delivery). Addressing cancer-induced morphologic (e.g., angiogenesis) or metabolic changes (e.g., tissue glycation) within the skin, several studies already document the applicability of optoacoustic imaging for diagnostic purposes [ 190 , 191 , 192 ] or potentially cancer-related changes of tissue glycation [ 193 ].…”
Section: And How Can We Measure Them?mentioning
confidence: 99%
“…Current therapeutic approaches are unable to target tumor cells due to increased stiffness resulting from abnormal extracellular matrix structural changes and a hypoxic tumor environment [ 200 ]. In this regard, the ability of L. lactis to detect melanoma using Multispectral Optoacoustic Tomography (MSOT) was investigated [ 156 ]. L. lactis was engineered to express β-galactosidase, a well-characterized MSOT contrast agent [ 201 ], under the Stress-Inducible Controlled Expression (SICE) system.…”
Section: Engineered Bacteria As Imaging Vectorsmentioning
confidence: 99%
“… Stritzker et al (2007 ) showed that some facultative anaerobes (e.g., Escherichia and Salmonella ) are able to sense the nutrient-rich region in and around the tumor center, which results in enhanced accumulation in tumors. Actually, these mechanisms are neither mutually exclusive nor completely independent, and bacteria might activate multiple pathways to specifically target tumors ( Garza-Morales et al, 2020 ). Certainly, different strains may exhibit distinct mechanisms lead to different tumor-targeting abilities.…”
Section: Foundation Of Bacteria-based Cancer Treatmentsmentioning
confidence: 99%